2020
DOI: 10.1002/ange.202002923
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Nitrogen towards Direct Nitrate Production on Spinel Oxides

Abstract: Nitrates are widely used as fertilizer and oxidizing agents. Commercial nitrate production from nitrogen involves high‐temperature‐high‐pressure multi‐step processes. Therefore, an alternative nitrate production method under ambient environment is of importance. Herein, an electrochemical nitrogen oxidation reaction (NOR) approach is developed to produce nitrate catalyzed by ZnFexCo2−xO4 spinel oxides. Theoretical and experimental results show Fe aids the formation of the first N−O bond on the *N site, while h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…20 Recently, a few experimental reports emerged suggesting Pd-decorated MXenes and several oxides as potential electrocatalysts for nitrogen oxidative xation. [21][22][23][24] Fig. 1 Equations showing how nitric acid is manufactured on industrial scale by combining steam reforming, Haber-Bosch and Ostwald processes.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recently, a few experimental reports emerged suggesting Pd-decorated MXenes and several oxides as potential electrocatalysts for nitrogen oxidative xation. [21][22][23][24] Fig. 1 Equations showing how nitric acid is manufactured on industrial scale by combining steam reforming, Haber-Bosch and Ostwald processes.…”
Section: Introductionmentioning
confidence: 99%
“…This superficial CoO(OH) enriched surface layer has a beneficial effect on the OER for the oxides. 55,62 However, in the presence of surface nitrogen based species, the stabilised CoO(OH) contribute to both the NOR and OER. 62 Kato and Kudo 63 looked at numerous tantalate oxide photocatalysts, and the authors observed nitrate reduction under UV irradiation in an aqueous environment.…”
Section: Surface Reconstruction Under Oer Conditions Has Previously Been Discussed Formentioning
confidence: 99%
“…The porous structure makes WO 3 to have more suspended bonds, activating high‐energy electrons to stimulate N≡N triple bond ( Figure 8A ) 117 . ZnFe x Co 2− x O 4 spinel oxides were also utilized as catalysts to carry out electrocatalytic NOR, 123 which achieved the direct synthesis of nitrate with high yield (130 ± 12 μmol/hr/g MO at 1.6 V vs RHE) by iron catalysts (Figure 8B,C). Besides, modified MXene electrocatalysts have also been utilized as electrocatalyst for NOR, which achieved 2.80 μg/hr/mg cat yield of nitrate (Figure 8D).…”
Section: Conversion Between Nitrogen and Nitrogen Oxidesmentioning
confidence: 99%
“…C, Relative energy diagram of NOR processes on ZnFe x Co 2‐ x O 4 spinel oxides ( x = 0, 0.4, and 2). Reproduced with permission: Copyright 2020, Wiley‐VCH 123 . D, Scanning electron microscopy, transmission electron microscopy, and high‐resolution transmission electron microscopy images of prepared Pd‐MXene, respectively.…”
Section: Conversion Between Nitrogen and Nitrogen Oxidesmentioning
confidence: 99%